Statistical parametric mapping of ground reaction forces during walking of aged adults - Neves, Ana Maria Bender Seidenfuss das (2021)
Statistical parametric mapping (SPM) acts along the acquisition time window and detects changes along the dimensions of a continuous n-dimensional field. The objective is to investigate the usability of the SPM in experimental data of ground reaction forces (GRF) during walking in elderly women, as well as to contribute to the expansion of the use of the method in biomechanics. For this, the study and execution of a preliminary stage of data preparation was carried out, followed by the traditional analysis with analysis of discrete points and continuous analysis (SPM), and finally the comparison of results between the methods and between the age groups (young, adult and elderly). Experimental data from two laboratories were included in this study. Concluding that it is possible to apply the method of continuous analysis in experimental data of GRF of the gait after a good preparation of the data is guaranteed, as well as the expansion of the numerical results for applications that help professionals in the areas of movement analysis. The methods presented convergent conclusions; however the continuous method expands the analysis, resulting in a greater range of information from a single test. There was a reduction in the amplitude of the GRF for elderly women in the internal data set (Laboratory of Assessment and Research in Physical Activity (LAPAFI - PUCRS)) when compared to groups of young people and adults in the external data set (GaitRec) during the phases of deceleration and acceleration of stance, and an increase in the phase of simple stance (medium stance), leading us to believe that these participants rely more on the stabilizing muscle group during gait. It is necessary to expand the application of the method and its dependencies (acquisition, preparation, and data management, for example).